Elevated gonadal atresia as biomarker of endocrine disruptors: Field and experimental studies using Mytilus trossulus (L.) and 17-alpha ethinylestradiol (EE2). Issue 1 (15th July 2017) - Smolarz, Katarzyna; Hallmann, Anna; Zabrzańska, Sandra; Pietrasik, Anna
Abstract: In the present work we compared the type and frequency of gonadal abnormalities among Mytilus trossulus populations from the Gulf of Gdańsk, Baltic Sea. Observed histopathologies were grouped as regressive changes (RC, gonadal atresia (GA) and regression (GR)), progressive changes (PC, gonadal tumors) and intersex. Sex-based and spatial differences in frequency of RC were found, with the highest frequency of RC and PC found in mussels from polluted station B followed by mussels from station A located near a purification plant outlet. Bivalves from the reference area had the lowest frequency of RC. In order to confirm biomarker applicability of RC, an exposure experiment with model xenoestrogen 17α-ethinylestradiol (EE2) was performed. The exposure of M. trossulus to 50 and 500 ng dL − 1 of EE2 resulted in an increased frequency of gonadal regression and atresia, including melanized hemocytes infiltration in seminiferous tubules. We thus suggest that these changes can serve as biomarkers of endocrine disrupting compounds in biomonitoring studies. Highlights: Progressive and regressive gonadal abnormalities were found in the blue mussel inhabiting polluted areas. Increased frequency of melanised hemocyte aggregates was observed in the mussels exposed to EE2. We suggest that these changes can serve as biomarkers in studies of endocrine disrupting compounds.